How Useful Is Universal Darwinism as a Framework to Study Competition and Industrial Evolution? - Guido Buenstorf (Max Planck Institute for Research into Economic Systems, 2005)
The adequate role of Darwinist concepts in evolutionary economics has long been a contentious issue. The controversy has recently been rekindled and modified by the position of "Universal Darwinism", most prominently favored by Geoffrey Hodgson and Thorbjørn Knudsen. They argue that the ontology of all evolutionary systems accords to the basic Darwinist scheme of variation, selection and inheritance. This paper focuses on the emerging application of the Universal Darwinist framework to the analysis of market competition and industrial evolution and gauges its usefulness for organizing an evolutionary approach to industrial economics. Drawing on both a theoretical discussion and recent empirical findings, it argues that selection and inheritance concepts narrowly construed after the biological example are of limited help in studying markets and industries. As an alternative to the "topdown" approach of Universal Darwinism, "bottom-up" causal theories are suggested that explain how the interplay of descent, experience and learning shapes the competitive performance of firms in the evolution of industries.
Keywords: L20; L10; B52; 330; Universal Darwinism; routines; pre-entry experience; spinoffs; descent; Evolutionsökonomik; Industrieller Strukturwandel; Interdisziplinäre Forschung